Influence of acidic type on nanostructures and electrochemical performance of polyaniline for flexible supercapacitors and improved performance based on 3D honeycomb-like nanosheet by doping HPF6 acid. (10th September 2021) - Zhou, Caixia; He, Shuai; Yang, Haocheng; An, Junjie; Yang, Lufa; Yan, Ping; Zhang, Hailong
Abstract: Designing and preparing polyaniline (PANI)-based flexible electrode materials with special nanostructure hold critical promise as capacitive materials. Here, the PANIs were synthesized in HCl, H2 SO4, phytic acid and HPF6 reaction systems with the same concentration via fast microwave-assisted chemical polymerization. Scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, UV-vis absorption spectroscopy, and X-ray photoelectron spectroscopy (XPS) were conducted to characterize their nanostructures and chemical compositions. Results reveal an apparent influence of acidic types on PANI morphology and nanostructures. The HPF6 -doped PANI/carbon cloth (F-PANI/CC) show the morphology of 3D honeycomb-like nanosheets and highly ordered phenazine-like oligomeric structure as well as higher homogeneous protonation of PANI backbones on the substrate of carbon cloth (CC). These main features favor the formation of rich electron centers, density of electric charges, and better contact and reaction between PANI materials and electrolyte. As a consequence, the assembled F-PANI/CC-based symmetric solid-state supercapacitor exhibits favorable electrochemical performance with a maximum energy density of 32.6 Wh kg −1 and a maximum power density of 1693 W kg −1 at a voltage window of 1.0 V compared with other PANI electrode materials. This work would inspire the HPF6 -doped PANI electrode materials for high-performance flexible supercapacitors. Graphical abstract: The flexible F-PANI/CC electrode has 3D honeycomb-like nanosheets and highly ordered phenazine-like oligomeric structure as well as higher homogeneous protonation of PANI backbones, which exhibits favorable electrochemical performance in flexible supercapacitors Image, graphical abstract